Legal aspects of changes in the calculation of the marisa national saving banks of marisa branch interest calculation methods - Nasrullah Nasrullah (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Banks as legal entities must also pursue profits. And one source of bank income is the interest on loan loans that have been channeled to customers. And if the bank's revenue target is threatened because the value of the rupiah weakens or floats, the bank is basically allowed to raise lending rates as long as it does not exceed the limit set by the government in this case the Financial Services Authority ... But the facts that occur in this case are not in context changes or adjustments in loan interest rates with rupiah value. But the change in the method of calculating credit interest rates from the type of effective calculation becomes an annuity calculation. So that changes in the method of calculating interest rates should not be done without an agreement from both parties.The Marisa Branch National Pension Savings Bank has carried out defaults since the first credit agreement, changes to the second credit agreement, and arrived at a change in the third credit agreement for changes in interest rates. Thus, of course this has legal consequences that must be borne by the party who defaults, in this case the National Pension Savings Bank. Then the actions of the bank are included in the category of actions that cause losses to debtors due to default of creditors (BTPN), so that the legal consequences can be by canceling the agreement along with guri change or by fulfilling the agreement accompanied by compensation.